A Review of the Histologic, Genetic and Molecular Characteristics of Meningioma Pathogenesis and Progression - Maurer Adrian; Archer Jacob; Safavi-Abbasi Sam; Sughrue Michael (Journal of Cancer Genetics And Biomarkers, 2017)
Meningiomas are the most common intracranial tumor in humans. The heterogeneity of these tumors lends difficulty to the genetic, epigenetic, and molecular changes that occur in meningioma pathogenesis, progression, and recurrence. Current de facto classification schemes are based on histologic evaluation of tumor specimens and do not consider molecular markers or other newer modalities. In this paper, we review the major genetic, epigenetic, and molecular changes that have been associated with the oncogenesis and progression of meningiomas. We pay special attention to those changes associated with recurrence and higher grade tumors. Finally, we comment on the challenges and potential for future therapies of these tumors.
Keywords: meningioma